Pengaruh Efektivitas Antibakteri Ekstrak Daun Kumis Kucing Terhadap Bakteri Streptococcus Mutans - Rizky Mulyanti; Member Reni Purba; Dian Soraya Tanjung; Shania Salsabila (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; Streptococcus mutans is a pathogenic bacteria and the main cause of dental caries. Swe needs a preventive measure for dental caries with natural antibacterial ingredients with cat whiskers. Aim; determine the effect of antibacterial effectiveness of cat whiskers leaf extract against streptococcus mutans bacteria. Method; The study used a laboratory experimental design with posttest only control group in vitro. The data was collected by measuring the diameter of the zone of inhibition using a shear caliper. Then, the data were analyzed using one-way ANOVA and posthoc LSD statistical tests. Result; that the average diameter of the inhibition zone of cat whiskers leaf extract (Orthosiphon stamineus) antibacterial with a concentration of 50%, 25%, 12.5%, 6.25%, 3.125% against Streptococcus mutans. bacteria were 11.50 ± 0.38 mm, 10.78 ± 0.22 mm, 9.90 ± 0.13 mm, 9.10 ± 0.08 mm and 8.25 ± 0.25 mm, while the control was negative. In this study, DMSO does not have an inhibitory diameter (0 mm). Conclusion; that there is antibacterial effectiveness of cat whiskers leaf extract against Streptococcus mutans bacteria